Childhood Obesity: Nutritional Transition of Bangladesh - Rahman, SM Tajdit; Islam, Md Daharul; Chowdhury, Ranajit Sen; Tarannum, Abida (Bangladesh Journal of Medicine, 2019)
Childhood obesity has been a major public health concern in many high income countries. In middle income countries, like Bangladesh, the coexistence of obesity and underweight makes the situation more grievous. It creates a transitional status in the childhood nutrition in Bangladesh. The priority is to identify the overall picture of obesity status in our country. In this review article we try to identify the transitional situation of childhood nutrition and the importance of finding out the overall picture of childhood obesity throughout the country. Bangladesh J Medicine Jan 2020; 31(1) : 37-38